2023
DOI: 10.1029/2022ja031157
|View full text |Cite
|
Sign up to set email alerts
|

First Detection of Midlatitude Plasma Bubble by SuperDARN During a Geomagnetic Storm on May 27 and 28, 2017

Abstract: We used the global navigation satellite system‐total electron content (TEC) and Super Dual Auroral Radar Network (SuperDARN) radar to elucidate the characteristics of the plasma bubble extending to midlatitudes over North America during a geomagnetic storm on 27 and 28 May 2017. To identify plasma bubbles, we analyzed the rate of the TEC index (ROTI), which is a good indicator of the occurrence of plasma bubbles. The enhanced ROTI region expanded up to 50°N (geomagnetic latitude), and the upper limit of this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…Similarly, Foster and Rich (1998) measured a distinct EPB‐like ionospheric depletion using the Millstone Hill incoherent scatter radar around 35–37° MLAT. Moreover, recent studies employing coordinated ground‐based observations and satellite in‐situ measurements have revealed that these bubble‐like plasma depletions can form poleward‐streaming structures that extend considerably across the midlatitude region, reaching unexpectedly subauroral latitudes of 40–50° MLAT, such as over the European longitude sector (Cherniak & Zakharenkova, 2016; Katamzi‐Joseph et al., 2017), Asian‐Pacific longitude sector (Aa et al., 2018; Huang et al., 2007; Li et al., 2018), and American longitude sector (e.g., Aa et al., 2019; Chang et al., 2022; Cherniak & Zakharenkova, 2022; Martinis et al., 2015; Sori et al., 2023; Zakharenkova & Cherniak, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Foster and Rich (1998) measured a distinct EPB‐like ionospheric depletion using the Millstone Hill incoherent scatter radar around 35–37° MLAT. Moreover, recent studies employing coordinated ground‐based observations and satellite in‐situ measurements have revealed that these bubble‐like plasma depletions can form poleward‐streaming structures that extend considerably across the midlatitude region, reaching unexpectedly subauroral latitudes of 40–50° MLAT, such as over the European longitude sector (Cherniak & Zakharenkova, 2016; Katamzi‐Joseph et al., 2017), Asian‐Pacific longitude sector (Aa et al., 2018; Huang et al., 2007; Li et al., 2018), and American longitude sector (e.g., Aa et al., 2019; Chang et al., 2022; Cherniak & Zakharenkova, 2022; Martinis et al., 2015; Sori et al., 2023; Zakharenkova & Cherniak, 2020).…”
Section: Introductionmentioning
confidence: 99%